Research on the application of Orff teaching method in music teaching in preschool education in colleges and universities in Hebei Province (Journal of Namibian Studies : History Politics Culture, 2023)
Preschool education plays an increasingly significant role as quality education is promoted Traditional methods of instruction are no longer able to motivate students to learn effectively Consequently, a new method of instruction is necessary for genuine music instruction In this paper, we devise a case study of three main courses in music for early childhood education and obtain the actual "learning efficacy" of the students through the distribution of questionnaires Then, this paper discusses the positive effects of Orff Method's teaching objectives, teaching contents, and teaching methods on students' interest in learning music, students' performance in learning music, and the classroom environment conducive to music learning The Orff Method has broad applicability in the instruction of music to preschool education majors at universities in Hebei Province and can effectively enhance the comprehensive music ability of preschool education majors The integration of the Orff Method better aligns the music skills curriculum with the characteristics of early childhood education It is more conducive to enhancing the application skills of preschool education students in order to cultivate a group of outstanding, composite early childhood education talent for society.